Copolymers and their use as coatings

By designing copolymers of general formula (I) and general formula (II), the problems of low molar mass and insolubleness of existing PPM-based copolymers are solved, and the solubleness and excellent material properties of high molar mass copolymers are achieved. They are suitable for the processing and application of industrial coatings, and have self-repair and good anti-corrosion properties.

CN119585338APending Publication Date: 2025-03-07ETH ZURICH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380055014.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-20
Filing Date
2023-07-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing poly(phenylenemethylene) (PPM)-based copolymers have low molar mass, are insoluble in any solvent, and are difficult to process, limiting their use in industrial applications.

Method used

By designing a copolymer containing general formula (I) and general formula (II), it is completely soluble in common organic solvents such as chloroform, dichloromethane or THF in a molar mass range of more than 100 kDa, and has high thermal stability, oxidation resistance and good barrier properties.

Benefits of technology

It realizes the solubleness and excellent material properties of high molar quality PPM-based copolymers, which are suitable for the processing and application of industrial coatings, and have self-repair and good corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585338A_ABST
    Figure CN119585338A_ABST
Patent Text Reader

Abstract

The invention relates to a copolymer and its use as a coating. The copolymer comprises a first monomer of general formula (I) and a second monomer of general formula (II) wherein in general formula (I) Z1 is selected from the group consisting of fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3), in general formula (II) Z2 is selected from the group consisting of fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3), and in general formula (II) Z3 is selected from the group consisting of fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3), y is selected from the group consisting of-CH2Z3, a linear or branched C1-C30 alkyl group, a linear or branched C2-C30 alkenyl group, a linear or branched C2-C30 alkynyl group, a sulfo group (-SO3H), a nitro group, an amino group, a hydroxyl group,-NHCOR5,-CONHR6,-OCOR7,-COOR8 and-OR9, wherein Z3 is selected from the group consisting of fluorine, chlorine, bromine, iodine, a hydroxyl group, toluene-4-sulfonyloxy group (-O-SO2-C6H4-CH3) and methylsulfonyloxy group (-O-SO2-CH3); wherein R5, R6, R7, R8, and R9 are selected from the group consisting of a linear or branched C1-C30 alkyl group, a linear or branched C2-C30 alkenyl group, and a linear or branched C2-C30 alkynyl group; and R1, R2, R3 and R4 are independently selected from the group consisting of a linear or branched C1-C30 alkyl group, a linear or branched C2-C30 alkenyl group, a linear or branched C2-C30 alkynyl group, a sulfo group (-SO3H), a nitro group, an amino group, a hydroxyl group, an oligomer (C2 to C4 alkylene glycol),-NHCOR5,-CONHR6,-OCOR7,-COOR8 and-OR9, wherein R5, R6, R7, R8 and R9 are selected from the group consisting of a linear or branched C1-C30 alkyl group, a linear or branched C2-C30 alkenyl group and a linear or branched C2-C30 alkynyl group. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a copolymer and use thereof as a coating.

[0002] Corrosion protection is one of the most important functions of organic coating compositions for metal substrates. On the one hand, the barrier function of the coating composition can be improved to keep corrosive agents, such as oxygen, water and ions, away from the metal surface. On the other hand, corrosion-inhibiting pigments can be used, which chemically or electrochemically intervene in the corrosion process, for example, by forming insoluble deposits with corrosion products or by passivating the metal surface.

[0003] Poly(phenylene methylene) (PPM) is a compound having the general formula (C6H4[CH2]) n A hydrocarbon polymer. It is structurally located between polyethylene and polyphenylene and consists of an alternating sequence of phenylene and methylene units. Remarkably, it exhibits a rather unique combination of material properties. In addition to high hydrophobicity, it is highly thermally stable and fluorescent. Such optical properties are unusual for non-conjugated polymers such as PPM (Marco F. D'Elia et al.; Poly(phenylene methylene)-Based Coatings for Corrosion Protection: Replacement of Additives by Use of Copolymers, 2019, 9, 3551; doi:10.3390 / app917355). PPM has also been shown to be effective in corrosion protection, however, only when mixed with rheological additives such as polysiloxane and benzyl butyl phthalate, as external plasticizers, to prevent surface cracking due to the stiffness of the polymer. In order to avoid the common problems associated with the use of external plasticizers, D'Elia et al. described the development of coatings based on PPM-related copolymers containing n-octoxy side chains and their anticorrosive properties. However, the copolymers have low molar mass, are insoluble in any solvents, and cannot be processed, which limits their industrial use.

[0004] Nemoto Tadamasa et al. (Synthesis and properties of organosoluble poly(phenylenemethylene)sfrom substituted benzenes or naphthalenes", POLYMER JOURNAL, Vol. 38, No. 12, November 16, 2006 (2006-11-16), pp. 1278-1282, XP093008488) disclose the synthesis of organic soluble substituted benzene or naphthalene-formaldehyde copolymers by addition-condensation.

[0005] US3265640A discloses a method for forming a shaped crosslinked polymer, which comprises reacting α,α'-dichloro-p-xylene and polysubstituted benzene in the presence of a catalytic amount of a Friedel-Crafts catalyst to form a soluble condensation polymer. et al. (Journal ofPolymer Science, 2018, 56, 309ff) disclose the synthesis and fractionation of 2,3,5,6-tetramethylbenzyl chloride in bulk polymerization in the presence of a dangerous SnCl4 catalyst. However, the synthesis produces an insoluble cross-linked polymer with a glass transition temperature of about room temperature, and a small amount of the soluble portion of the material shows a molar mass of less than 800Da. In addition, it is necessary to preheat the solid monomer at 80°C, and polymerization only occurs after heating at 180°C for 1 hour. Therefore, the polymer is not suitable for industrial applications.

[0006] It is an object of the present invention to provide a PPM-based copolymer of high molar mass which is soluble in common organic solvents (ie easy to process).

[0007] This problem is solved by a copolymer according to claim 1. Further preferred embodiments are subject matter of the dependent claims.

[0008] It was found that the copolymer of the present invention comprising a first monomer of general formula (I) and a second monomer of general formula (II) can be obtained with a molar mass higher than 100 kDa and is completely soluble in common organic solvents such as chloroform, dichloromethane or THF. In addition, the copolymer has an excellent combination of material properties, namely high thermal stability, oxidation resistance and good barrier properties. In addition, the fluorescence of the copolymer of the present invention helps to detect corrosion or failure of the coating in any other barrier / coating application.

[0009] Furthermore, the copolymers according to the invention are thermoplastic. This allows the copolymers to be processed by all the strategies employed with other thermoplastic polymers, which is a significant advantage for their industrial use, since, for example, in the area of ​​corrosion protection, almost all commercially available coatings are thermosetting resins. Furthermore, the reversible thermoplastic properties of the copolymers according to the invention allow the structure to be restored after a thermal shock (e.g., can be used for self-repair).

[0010] Furthermore, the complete substitution of the phenylene rings in the monomers of general formula (II) does not allow any reaction on the aromatic backbone and prevents the formation of a complex three-dimensional network, providing a completely soluble thermoplastic copolymer with enhanced material properties due to the insertion of side chains.

[0011] The copolymer of the present invention comprises:

[0012] The first monomer of formula (I)

[0013]

[0014] wherein Z1 is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3), and

[0015] The second monomer of formula (II)

[0016]

[0017] in

[0018] Z2 is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3),

[0019] Y is selected from -CH2Z3, straight chain or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxy, -NHCOR5, -CONHR6, -OCOR7, -COOR8 and -OR9,

[0020] wherein Z3 is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3);

[0021] Wherein R5, R6, R7, R8 and R9 are selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C30 alkynyl; and

[0022] R1, R2, R3 and R4 are independently selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxyl, oligo (C2 to C4 alkylene glycol), -NHCOR5, -CONHR6, -OCOR7, -COOR8 and -OR9, wherein R5, R6, R7, R8 and R9 are selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 Alkynyl.

[0023] The “C1-C 30 "Alkyl" means an aliphatic hydrocarbon group which may be straight or branched and containing from 1 to 30 carbon atoms in the chain. "Branched" means that one or more lower alkyl groups such as methyl, ethyl or propyl are attached to a straight alkyl chain.

[0024] “C2-C 30 "Alkenyl" means an aliphatic hydrocarbon group containing at least one carbon-carbon double bond and which may be straight or branched and comprising from 2 to 30 carbon atoms in the chain. "Branched" means that one or more lower alkyl groups (such as methyl, ethyl or propyl) are attached to a straight alkenyl chain.

[0025] “C2-C 30 "Alkynyl" refers to an aliphatic hydrocarbon group containing at least one carbon-carbon triple bond and which may be straight or branched and comprising from 2 to 30 carbon atoms in the chain. "Branched" means that one or more lower alkyl groups such as methyl, ethyl or propyl are attached to a straight alkynyl chain.

[0026] “C2 to C4-oligo(alkylene glycol)” refers to oligomers composed of a small amount of alkylene glycol repeating units, such as oligo(ethylene glycol), oligo(propylene glycol) and oligo(ethylene glycol / propylene glycol). The alkylene repeating unit may be linear or branched and have 2 to 4 carbon atoms. The number of repeating units is 1 to 10, preferably 1 to 5. For example, the molecular formula of oligo(ethylene glycol) is –(CH2CH2O)p1-H, and P1 is an integer from 1 to 10, preferably an integer from 1 to 5. For example, the molecular formula of oligo(propylene glycol) is –(CH(CH3)CH2O)p2-H or –(CH2CH2CH2O)p2-H, and p2 is an integer from 1 to 10, preferably an integer from 1 to 5. Oligomer (ethylene glycol / propylene glycol) refers to an oligomer having a mixture of ethylene glycol and propylene glycol units in its repeating units. The term "monomer" refers to a low molecular weight reactive substance that chemically bonds with other molecules, especially other monomers, to form a polymer. In this case, each monomer contains at least one leaving group.

[0027] The term "copolymer" refers to a compound containing multiple monomers in a linear or branched chain, which contains two or more different monomers.

[0028] The term "bimodal" means that the claimed compound has at least two polymer or copolymer components with a weight average molecular weight (Mw) difference of at least 50,000 g / mol (referred to herein as "ΔMw") as measured by GPC (gel permeation chromatography) as described herein, but is not limited to compounds that show two or more visible peaks or humps in the curve produced by the chromatograph. Thus, in the context of the present invention, a unimodal phase comprising polymers with molar masses of 100,000 g / mol and 150,000 g / mol is also considered bimodal.

[0029] The term “M n "(Number average molar mass)" refers to the total mass of all polymer chains in a sample divided by the total number of chains in the sample and is determined by size exclusion chromatography (SEC).

[0030] The term “M w By "mass average molar mass (or weight average molar mass)" is meant the average of the molar masses of all chains, weighted by the mass of chains of each length and determined by size exclusion chromatography (SEC).

[0031] The term "PDI" refers to the polydispersity index, equivalent to the term "MWD" (molecular weight distribution), which is determined by using size exclusion chromatography (SEC).

[0032] Preferably, the second monomer in the copolymer of the present invention has the general formula (IIa)

[0033]

[0034] in

[0035] Z2 is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3),

[0036] Z3 is selected from fluorine, chlorine, bromine, iodine, hydroxy, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3); and

[0037] R1, R2, R3 and R4 are independently selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxyl, oligo(ethylene glycol), -NHCOR5, -CONHR6, -OCOR7, -COOR8 and -OR9, wherein R5, R6, R7, R8 and R9 are selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 Alkynyl.

[0038] Due to the presence of two reactive groups -CH2Z2 and -CH2Z3, wherein Z2 and Z3 are preferably identical, the monomer of general formula (IIa) acts as a co-catalyst. The results show that the bifunctionality of the monomer significantly increases the yield of copolymers with high molar mass and high PDI values. In addition, the study shows that the presence of the monomer of general formula (II) has no negative impact on the connectivity of the polymer backbone.

[0039] Z1, Z2 and Z3 act as leaving groups. The power of the leaving group generally increases from chlorine to bromine to iodine; however, chlorine is preferred due to its better availability. Suitable sulfonyloxy groups (residues -SO3 -) as leaving groups for suitable sulfonates (i.e. sulfonates) are attractive alternatives to halogen groups, especially when the residue is electron withdrawing. They can be conveniently prepared from numerous commercially available derivatives, and they show similar reactivity to halogens. Examples of suitable sulfonyloxy groups are toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3; i.e. the monomer is p-toluenesulfonate (p-toluenesulfonate), synonym: tosylate), methylsulfonyloxy (-O-SO2-CH3; i.e. the monomer is methanesulfonate (methanesulfonate), synonym: mesylate) or trifluoromethylsulfonyloxy (-O-SO2-CF3; i.e. the monomer is trifluoromethanesulfonate (trifluoromethanesulfonate), synonym: triflate).

[0040] In a preferred embodiment, Z1, Z2 and Z3 in the monomers of formula (I) and (II) are identical, which makes the reaction more controllable, the crude product easier to process and to purify from by-products generated by the leaving group.

[0041] Particularly good results are obtained when the second monomer of the general formula (IIa) has the same R1, R2, R3 and R4, in particular when Z2 and Z3 are chloro groups (α,α-bischloromethyldurene):

[0042]

[0043] The results show that the presence of α,α-bis(chloromethyl)durene does not affect the initiation temperature of the polymerization below 150°C. However, at temperatures above 150°C, α,α-bis(chloromethyl)durene affects the reaction kinetics by increasing the monomer conversion. The increase in monomer conversion leads to an increase in the viscosity of the reaction batch.

[0044] In another embodiment of the present invention, the copolymer may contain one or more additional monomers of formula (III)

[0045]

[0046] in

[0047] Z2' is selected from fluorine, chlorine, bromine, iodine, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyl (-SO2-CH3),

[0048] Y' is selected from -CH2Z3', straight chain or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30Alkynyl, sulfo (-SO3H), nitro, amino, hydroxyl, -NHCOR5', -CONHR6', -OCOR7', -COOR8' and -OR9',

[0049] wherein Z3' is selected from fluorine, chlorine, bromine, iodine, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3);

[0050] wherein R5', R6', R7', R8' and R9' are selected from a linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 alkynyl; and

[0051] R1', R2', R3' and R4' are independently selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxyl, oligo(C2 to C4 alkylene glycol), -NHCOR5', -CONHR6', -OCOR7', -COOR8' and -OR9', wherein R5', R6', R7', R8' and R9' are selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 Alkynyl, and

[0052] The monomer of general formula (III) is different from the monomer of general formula (II).

[0053] For example, such additional monomers can be added to adjust the rheological properties of the coating.

[0054] Preferably, in the compounds of Formula II and Formula IIa, at least one of R1, R2, R3 and R4 is selected from a linear or branched C8-C 30 Alkyl, straight chain or branched C8-C 30 Alkenyl, straight or branched C8-C 30 Alkynyl and -OR9, wherein R9 is selected from a linear or branched C8-C 30 Alkyl, linear or branched C8-C 30 Alkenyl and straight or branched C8-C 30 In a particularly preferred embodiment, one of R1, R2, R3 and R4 is -OR9, wherein R9 is selected from a linear or branched C8-C 12Alkyl, preferably octyl, and the remaining residues are C1-C5 alkyl, preferably methyl. Such copolymers result in softer materials that are more easily deformed. Such copolymers can be easily processed by different methods and exhibit self-healing properties by exploiting the thermodynamics of corrosion reactions. In addition, they are suitable for low temperature applications.

[0055] In one embodiment of the present invention, the copolymer comprises 0.01% (mol / mol) to 5% (mol / mol), preferably 0.1% (mol / mol) to 1% (mol / mol"), most preferably 0.5% (mol / mol") of the monomer of the general formula (II). The concentration of the monomer of the general formula (II) can control the molecular weight. However, too high a concentration may produce highly crosslinked polymers. A low molar ratio of monomer of formula (II) to monomer of formula (I) of 0.1% (mol / mol) to 1% (mol / mol), most preferably 0.5% (mol / mol), allows the copolymer of the present invention to have a high molar mass.

[0056] Another aspect of the present invention relates to a method for preparing a copolymer according to the present invention. The copolymer is obtained by reacting a monomer of general formula (I) and a monomer of general formula (II) in the presence of a Lewis acid catalyst. The term "Lewis acid" as used herein refers to a substance that can accept an unshared electron pair from another molecule.

[0057] The amount of Lewis acid used depends on the required reaction time and the concentration of the monomer of general formula (II). Typically, for each equivalent of monomer of general formula (I) in the reaction mixture, the catalytic amount added is 0 wt % to 1.5 wt % equivalent of Lewis acid. The optimal amount of Lewis acid also depends on the catalyst.

[0058] Preferably, the reaction is carried out in the presence of a catalyst selected from bismuth (III) based catalysts, molybdenum based catalysts and tungsten based catalysts. It can be shown that the catalyst is more effective than the tin catalysts used in the prior art. The catalyst requires a shorter reaction time to maximize the monomer conversion. Most preferably, the catalyst is selected from WCl4(CNMe)2, WBr2(CO)3(dme), WCl4(THF)2 and MoI2(CO)3(MeCN)2, all of which show similar catalytic performance by step-growth polymerization (wherein CNMe is acetonitrile and dme is dimethoxyethane). For example, the copolymerization of benzyl chloride in the presence of α,α-bischloromethyldurene (0.5% mol / mol) catalyzed by WCl4(THF)2 gives monomers with a number average molar mass greater than 230,000 g mol -1The copolymers of the invention are soluble in organic solvents despite their high molecular weight, which is in contrast to other copolymerization or catalysis strategies reported in the literature, in which insoluble and therefore unprocessable polymers are obtained. In addition, the catalysts are present in solid form at room temperature, while SnCl4 is a toxic liquid that is difficult to handle.

[0059] In one embodiment of the invention, the copolymer is prepared in the presence of a catalyst during the entire polymerization process and the monomers of the general formula (II) are not added before at least 40% by weight of the monomers of the general formula (I) have reacted. This allows for efficient mixing, since an increase in viscosity would lead to a Weissenberg effect, which would result in ineffective mixing. Due to the thermoplastic properties of the copolymers according to the invention, this problem can be overcome by increasing the reaction temperature.

[0060] Furthermore, monomer I serves as a solvent for monomer II, i.e. the copolymerization reaction can be carried out without another solvent, which is of course both economical and environmentally friendly.

[0061] Preferably, the copolymerization reaction is carried out at a temperature of 80° C. to 180° C. Furthermore, no preheating of the monomers is required. No preheating treatment is required because benzyl chloride also acts as a solvent for the monomers of formula II, in particular BCMD.

[0062] BCMD (3,6-bis(chloromethyl)durene) is preferably added at 0.1% to 1% (mol / mol) relative to benzyl chloride. The reaction kinetics depends on the catalyst used and the concentration of BCMD in the polymerization batch. The product of this copolymerization can obtain a polymer with a high molar mass (above a number average molar mass of 100 KDa).

[0063] The copolymers according to the invention can be used as coatings, in particular as coatings for metal substrates. Using the copolymers according to the invention, a continuous, essentially crack-free layer is provided. Interestingly, no additional plasticizer is required. The coating comprising the copolymers according to the invention forms an excellent barrier between the substrate metal material and the surrounding environment, thereby inhibiting the corrosion process. This coating is an anti-corrosion layer with excellent coating adhesion, in accordance with ISO 17463:2014 standard, and has very good rheological properties. In addition, the rheological properties of the copolymers according to the invention allow inherent self-repairing, possibly by flowing, thereby closing pores in the polymer matrix that induce localized corrosion events or that are formed after localized corrosion events. This property gives the coating of the copolymer according to the invention an enhanced anti-corrosion ability, thereby improving the durability and effectiveness of the coating.

[0064] The thickness of the coating can vary and be adapted to the field of application. Preferably, it has a size of 5 μm to 600 μm, preferably 5 μm to 50 μm. With such a coating thickness, good corrosion protection in accordance with ISO 17463:2014 can be provided to the metal substrate. According to the procedure outlined in ISO 17463:2014, by testing the pre-damaged coating (circular damage ) also demonstrates these properties. The copolymers according to the invention allow coatings with smaller thicknesses, for example 5 μm to 50 μm, while for example epoxy resin coatings typically have a thickness of 200 μm to 600 μm. The reduced thickness leads to lower material costs and has a positive impact on the environment.

[0065] The commonly used materials of the substrate according to the present embodiment are aluminum and aluminum alloys, iron and steel (galvanized or ungalvanized) materials, and other examples thereof include copper-based materials and nickel-based materials. The substrate can be pretreated before coating, for example, by chemical pretreatment, particularly chromate treatment, chromium-free pretreatment, particularly phosphating or anodizing or silanization. The surface of the steel can be pre-coated with metals such as zinc. The shape of the substrate can be freely selected, and the substrate can be a primary processed product, such as a sheet, a rod and a pipe, or a secondary processed product, such as a bolt, a nut, a hinge, an engine block, a gasket and a housing. The processing examples of this secondary processed product include cutting / grinding, stamping, bending, cutting, casting, forging and other processing.

[0066] Preferably, the copolymer according to the invention is used as an anticorrosive. The corrosive environment may be, for example, an acidic, alkaline and salt environment. Such coatings are preferably used for commercial equipment, electrical equipment, automobiles, ships, bridges, aircraft, and in particular for secondary manufactured parts, such as fasteners including bolts and nuts, accessories including clamps and clips, and die-cast products including plates, housings, hinges and panels. These components require high precision during assembly, while their coatings have high strength and adhesion, because they may be subject to large shear forces during manufacture and assembly.

[0067] The copolymers according to the invention can be prepared as powders that can be easily stored and transported. The powder can be heated to the desired temperature and the molten product can then be applied to the substrate to be coated. The cooling process causes the molten material to harden and gain strength, forming a coating on the substrate. Because thermoplastic powder coatings can be reheated multiple times, they can be easily redistributed along the surface. This property allows defects in the coating to be easily repaired by heating.

[0068] Another embodiment of the present invention relates to a paint comprising a copolymer according to the present invention. This paint produces a coating that can simultaneously act as an adhesive, inhibitory and (self-repairing) protective layer. The coating formed is strong and self-curing, does not require an additional protective lacquer / paint outer coating under normal environmental conditions, and can be used as the topmost paint layer. In addition, the coating can be used as a primer because it can be easily coated with various paints to adjust its final color or provide additional protection for it. When the coating is used under severe corrosive environmental conditions, for example, when the coated object is a pipeline for corrosive chemicals, this additional protection may be required. In addition, the paint comprising the copolymer according to the present invention dries quickly after application and ensures sufficient pot life so that it can be used regardless of the season and temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1a The monomer conversion process in the presence of WCl4(THF)2 and the operating temperature as a function of reaction time are shown.

[0070] Figure 1b Shown is a gel permeation chromatogram of an aliquot taken during the reaction, revealing the evolution of a trimodal molar mass distribution. The sign of the curve is the same as Figure 1a The signs of monomer conversions are consistent.

[0071] Figure 2 Shown are gel permeation chromatograms of the synthesis of poly(phenylene methylene) using different catalysts.

[0072] Figure 3 The PPM synthesized with each catalyst is shown. 13 Comparison of C NMR signals. These peaks belong to the respective substitution patterns of the phenylene rings.

[0073] Figure 4a The monomer conversion process and the operating temperature as a function of reaction time in the presence of BCMD are shown.

[0074] Figure 4b Shown is a gel permeation chromatogram of an aliquot taken during the reaction, revealing the evolution of a trimodal molar mass distribution. The sign of the curve is the same as Figure 4a The signs of monomer conversions are consistent.

[0075] Figure 5 It shows that the low molar mass fraction (F 低 , squares) and high molar mass (high, circles) gel permeation chromatograms.

[0076] Figure 6 The normalized values ​​of PPM copolymer (squares) and PPM homopolymer (circles) are shown. 13 Comparison of C NMR signals.

[0077] Figure 7 Accelerated Cycle Electrochemical Technique (ACET) results are shown for a 30 μm thick coating of PPM containing octoxy side chains according to the prior art.

[0078] Figure 8 Accelerated Cycle Electrochemical Technique (ACET) results are shown for a pre-damaged 30 μm thick coating PPM containing octoxy side chains according to the prior art.

[0079] Fig. 9 Accelerated Cycle Electrochemical Technique (ACET) results are shown for a 30 μm thick coating with a copolymer according to the present invention.

[0080] Fig.10 Accelerated Cycle Electrochemical Technique (ACET) results are shown for a pre-damaged 30 μm thick coating with a copolymer according to the present invention. Example

[0081] Synthesis of poly(phenylene methylene) catalyzed by W and Mo complexes

[0082] The polymerization of benzyl chloride was carried out at a monomer to catalyst ratio of about 0.1% mol / mol per catalyst. Although the polymerization conditions were essentially based on et al. (Journal of Polymer Science, 2018, 56309ff), but in order to mitigate the viscosity increase and effectively mix during the reaction, the reaction temperature of the catalytic system applied here must be adjusted from room temperature to 80°C, 120°C, 160°C and 180°C independently of the time limit. An example of polymerization catalyzed by [WCl4(THF)2] is provided below. Under reduced pressure (approximately 10 -2 bar) from benzyl chloride to remove the stabilizer propylene oxide present in the starting material overnight. In a 50 mL three-necked flask, 20 g of benzyl chloride (20.8 mL, 0.16 mol) was added to the solid catalyst [WCl4(THF)2] (70 mg, 0.1 mmol) under nitrogen atmosphere and maintained at 15 mL min. -1 The crude reaction product was then stirred for 3 h under mechanical stirring to ensure good mixing between the catalyst and the monomer. During the reaction, the temperature was increased from 25 ° C to 180 ° C to enable mixing when the viscosity increased due to the increase in molar mass. After the reaction was completed, the molten polymer was cooled to room temperature. The product was purified by dissolving the polymer in 30 mL of chloroform and then pouring the solution into 600 mL of methanol. The suspension was vigorously stirred for 3 h. The PPM powder obtained was then filtered on a cellulose filter and the polymer powder was concentrated under vacuum (about 10 -2bar) overnight to obtain 6.3 g of a light yellow polymer (yield 66%). 1 H NMR (300 MHz, CDCl3, δ in ppm): 3.79 (broad, 2H), 7 (broad, 4H). GPC (THF). The molar masses are given in Table 1, 13 The C NMR spectrum is shown below.

[0083] Similar syntheses were performed using catalysts [WCl4(MeCN)2], [WBr2(CO)3(dme)], [MoI2(CO)3(MeCN)2]. The yields of purified PPM polymers ranged from 68% to 77% in total and are shown in Table 1 together with the molar masses.

[0084] Table 1. Number average molar masses (M) of polymers synthesized using W and Mo based catalysts n ), weight average molar mass (M w ), polydispersity index (PDI) and reaction yield.

[0085]

[0086]

[0087] Synthesis of Poly(phenylene methylene) Copolymers Catalyzed by WCl4(THF)2

[0088] As described above, in the presence of 0.5% mol / mol 1,4-bis(chloromethyl)-2,3,5,6-tetramethylbenzene (3,6-bis(chloromethyl)durene, BCMD), [W2Cl4(THF)2] (75 mg, 0.16 mmol) was used as a catalyst to prepare 172 mg of BCMD (7.4·10 -1 mmol) was added to 17 mL of benzyl chloride (148 mmol) to synthesize PPM with durene units. The color change during the reaction was as follows: clear yellow-brown in the first minute, black at 80°C, blue at 120°C, and dark green at 160°C. After the PPM was sampled as described above, 6.63 g (82%) of a blue-green product was obtained. 1 H NMR (300MHz, CDCl3, δ unit ppm): 2.5 (s, 0.12H, CH3) 3.71 (br, 2H, CH2), 7.19 (br, 4H, Ar); GPC (CHCl3): M n =3,400 g mol -1 , weight average molar mass (M w ) = 211,977 g mol -1 , M w / M n=55.4;DSC(T g ):52.0℃.

[0089] Phase separation fractionation

[0090] The copolymer (1 g) (M n =3,317 g mol -1 , M w =183,600 g mol -1 ) and 2-butanone (23 mL) were stirred vigorously for 2 h, after which the suspension separated into a clear upper phase (F 低 ) and containing high molar mass polymers (F 中间 ) of a turbid oil phase. The upper and lower phases were separated, the solvent removed on a rotary evaporator, and then redissolved in 5 mL of chloroform. The solution was precipitated in 200 mL of methanol with stirring, and the solid was filtered and dried (as described above) to obtain 0.452 g (45% fractional yield) of F 中间 (M n =33,520 g mol -1 , M w =322,000 g mol -1 ) (When the fractionation process was repeated twice, no fractions with higher molar mass could be separated). Thereafter, 50 mg of F was further washed with 5 mL of a mixture of chloroform / 2-butanone (volume ratio 1:1). 中间 , to remove the lower molar mass fraction and provide the polymer fraction F 高 (23 mg, fractional yield 46%) (M n =205,300 g mol -1 , M w =777,900 g mol -1 ).

[0091] Characterization

[0092] Recorded on a Bruker AV300 MHz spectrometer using CDCl3 as solvent 1 HNMR and 13 C NMR spectra. For broad signals, the multiplicities of the peaks are indicated as (bs), (s) singlet, (d) doublet, (t) triplet, and (m) multiplet. According to the literature, the reaction was performed by taking aliquots of the reaction mixture during the reaction. 1 The monomer conversion χ was evaluated by H NMR spectroscopy. The molar mass was investigated by gel permeation chromatography (GPC) using a Viscotek GPC system with tetrahydrofuran (THF) as eluent. The GPC module included a pump and a degassing system (GPCmax VE2001; 1.0 mL min -1flow rate), Viscotek 302 TDA as detector and two columns for analyzing different molar masses (2×PLGel Mix-B; size 7.5 mm×300 mm). Thermal characterization was performed using a TGA / DSC 3+ module (Mettler Toledo). The column was flushed with nitrogen (50 mL min -1 ) at 10℃min -1 The thermal transition from 25°C to 360°C was studied by increasing the temperature at a rate of 1.5 % and 2.5 % respectively. In the temperature range of 25°C to 900°C, the -1 ) at 10℃min -1 The heating rate is used to assess the onset of decomposition.

[0093] Evaluation of Catalytic Activity in the Homopolymerization of Benzyl Chloride

[0094] [WCl4(MeCN)2], [WCl4(THF)2], [WBr2(CO)3(dme)], [WBr2(CO)3(dme)] were screened as catalysts for the bulk polymerization of benzyl chloride, keeping the same catalyst / monomer molar ratio for all compounds (0.1% mol / mol). The catalysts were allowed to dissolve in benzyl chloride at room temperature before the temperature was raised and the reaction started. Due to the different solubility of each catalyst in benzyl chloride, the dissolution times for [MoI2(CO)3(MeCN)2] and [WBr2(CO)3(dme)] were in the range of minutes, while the W(IV)-based catalyst required 4 hours. The reaction temperature was then adjusted during the polymerization to avoid mixing problems caused by increased viscosity (i.e., the Weissenberg effect). The temperature required for the polymerization and the subsequent monomer conversion depended strongly on the compound. In particular, the polymerization reaction in the presence of [MoI2(CO)3(MeCN)2] was already initiated at 80°C, quickly (10 min) reaching a monomer conversion of about 90%. When [WCl4(MeCN)2] was used, the monomer conversion rate increased significantly between 80°C and 120°C, and stabilized at more than 80% after 5 h at this temperature. Previously reported W(II)-based catalysts also showed catalytic activity below 120°C, in contrast, polymerization catalyzed by [WCl4(THF)2] or [WBr2(CO)3(dme)] was initiated only at temperatures at or above 150°C.

[0095] After 5 h at 150 °C, the monomer conversion of the polymerization catalyzed by [WBr2(CO)3(dme)] reached 100%. It is noteworthy that no significant increase in viscosity was observed at this temperature, which may be due to the lower molar mass of the obtained polymer. On the other hand, the monomer conversion of the polymerization catalyzed by [WCl4(THF)2] at 150 °C dropped below 10% after 17 h. Increasing the temperature to 180 °C is essential to increase the monomer conversion and complete the reaction, as Figure 1a The figure shows an aliquot of a reaction mixture taken from the 1 Monomer conversion was obtained from H NMR spectroscopy. Figure 1b GPC chromatograms of aliquots sampled after various monomer conversions are shown. These chromatograms reveal that after initiation of the reaction at 150°C with 2% monomer conversion, a bimodal molar mass distribution appears with a peak at 15.4 min corresponding to 4,500 g mol -1 Up to 63,000 g mol -1 The molar mass of -1 After 17 h at this temperature, the two peaks shifted to lower retention times, 14.3 min and 15.4 min, and both had molar masses of 4,000 g mol -1 Up to 500,000 g mol -1 These chromatograms show a tail after 17 min, corresponding to the monomers and oligomers still present in the reaction batch at this monomer conversion. When the temperature is increased to 180 °C, the oligomer fraction grows faster relative to the high molar mass fraction, reflecting the rise of the 16.3 min peak, thus increasing with increasing monomer conversion. n Significantly reduced ( Figure 1b ). For other tungsten-based catalysts, the opposite was observed.

[0096] The presence of high molar masses at low monomer conversions suggests that a chain growth mechanism is involved in the presence of [WCl4(THF)2] (chain growth processes have also been reported for other tungsten-based catalysts). In contrast, this effect was not observed in the polymerizations using [WCl4(MeCN)2], [WBr2(CO)3(dme)], and [MoI2(CO)3(MeCN)2].

[0097] After isolating the polymer by dissolution and subsequent precipitation, the polymers ( Figure 2 ) exhibits a unimodal molar mass distribution, M n3,100 g mol -1 Up to 4,500 g mol -1 , M w 7,000 g mol -1 Up to 13,000 g mol -1 (Table 1), which is within the conventional range of PPM (see Introduction). However, the PPM obtained using [WCl4(MeCN)2] shows a bimodal molar mass distribution (Error! Reference source not found.), M n 4,090 g mol -1 , consistent with other catalysts, but M w Higher (63,760 g mol -1 ), so the PDI is higher (15.6) (Table 1).

[0098] Table 2. Number average molar masses (M) of polymers synthesized using W and Mo based catalysts n ), weight average molar mass (M w ), polydispersity index (PDI) and reaction yield.

[0099]

[0100] Among the catalysts studied, Mo(II)-based complexes and [WCl4(THF)2]-derived M n 25% to 30% higher than other tungsten catalysts. However, we believe that this and the higher M obtained with [WCl4(THF)2] w This is a specific effect of the compounds used rather than a general property of the platinum-based or W(IV)-based catalysts, especially since the catalysts have different operating temperatures.

[0101] Purified PPM 13 The C NMR spectrum corresponds to the spectra reported for other catalysts at PPM. The signal between 33 ppm and 44 ppm ( Figure 3 ) is attributed to the substitution pattern along the ppm backbone, as previously reported (in the aromatic region from 125 ppm to 145 ppm 13 C NMR signals are shown in the Supporting Information (SI.1). 1 H NMR spectra (Supporting Information (SI.2)) showed a broad peak at 3.7 ppm for the methylene region and a broad peak at 6.5 ppm to 7.25 ppm for the phenylene region of each polymer. PPMs obtained using SnCl4 or W(II)-based catalysts were also reported.

[0102] The obtained polymers were investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). All polymers showed high thermal stability with decomposition temperatures above 400 °C. In addition, the glass transition temperature was found to be between 58 °C and 63 °C, and no further first-order thermal transitions were detected. Therefore, the thermal properties of the obtained polymers are consistent with the PPM data obtained with other catalysts such as SnCl4 or W(II)-based complexes (T g 60℃ to 65℃, starts to decompose above 400℃).

[0103] Effect of α,α'-bis(chloromethyl)durene on Connectivity

[0104] Based on the results obtained with the above catalysts, [WCl4(THF)2] was selected to increase the molar mass with the bifunctional branching agent BCMD as a comonomer, since [WCl4(THF)2] provides the highest M w .like Figure 4a As shown, the presence of BCMD (0.5% mol / mol) does not affect the initiation temperature of the polymerization (no reaction below 150°C), but when the temperature reaches 150°C, the reaction becomes faster than the homopolymerization reaction. While in the case of homopolymerization, the monomer conversion does not exceed 10% at 150°C, at the same temperature, the monomer conversion reaches 70% in the presence of BCMD, accompanied by an increase in viscosity, which is reflected in the observation of the Weissenberg effect. Therefore, in order to ensure proper mixing in the polymerization batch, the temperature is increased to 180°C until the monomer conversion is complete. Figure 4b The chromatogram shown in FIG again shows the multimodal distribution of molar masses that occurs during polymerization, with the peaks generally shifting toward higher molar masses. It is noteworthy that, unlike homopolymerization, in the presence of a branching agent, the high molar mass peak (M n 914,800 g mol -1 ) increases with the increase of monomer conversion. n (3,400 g mol -1 ) did not change significantly, but M w (212,000 g mol -1 ) increased by 4 times relative to the homopolymer. The product containing BCMD was isolated by dissolution and subsequent precipitation to the corresponding homopolymer described above. Compared with the in situ product, the isolated product has essentially the same M n (3,400 g mol -1 ), but M w Slightly lower (187,900 g mol -1 ). On the other hand, M w Compared with the product without BCMD, w3.8 times higher, indicating that a higher proportion of high molar mass products was obtained with BCMD. In order to isolate the highest molar mass fraction, the obtained polymer was dissolved in 2-butanone, resulting in a fraction corresponding to the lower molar mass fraction (F 低 ) and the higher molar mass fraction (F 中间 ) was spontaneously separated by PPM fractionation as reported elsewhere. In addition, F was further extracted with a 1:1 (volume ratio) mixture of chloroform and 2-butanone. 中间 The lower mass polymer in the fraction is obtained as F 高 The fractionation results are shown in Table 3. 中间 M n (33,520 g mol -1 ) is one order of magnitude higher than the value before fractionation and also one order of magnitude higher than the value usually obtained from PPM (see Introduction). Fraction F 高 (205,300 g mol -1 ) n This even exceeds the highest molar mass of PPM isolated to date (167,900 g mol -1 , also obtained by fractionation). GPC chart ( Figure 5 ) also shows that the minimum molar mass (F 低 ) and the maximum molar mass (F 高 ) fractions are completely separated. Figure 5 It can also be clearly seen that F 高 Consists of a bimodal molar mass distribution with two peaks representing 872,000 g mol -1 and 122,200 g mol -1 However, our attempts to separate these two fractions to obtain a fraction with an ultra-high molar mass failed.

[0105] Table 3. Number average molar mass (M n ), weight average molar mass (M w ), polydispersity index (PDI), fractionation yield and the composition of the polymer fraction obtained by polymerization of benzyl chloride with 0.5% mol / mol BCMD catalyzed by [WCl4(THF)2] to obtain fraction F 低 、F 中间 、F 高 (See text).

[0106]

[0107] exist 13 In the C NMR spectra, the main difference between the products obtained with and without BCMD was the appearance of a peak at 16.5 ppm ( Figure 6), corresponding to the signal of the methyl group belonging to the durene unit, confirming that the durene unit has been incorporated into the polymer chain. 13 CNMR spectra showed slight differences in the substitution pattern between the copolymer and the homopolymer ( Figure 6 ). Essentially, the relative intensity of the ortho-ortho substitution pattern increases. 1 In the H NMR spectrum, unique signals of PPM (broad peak at 3.7 ppm and peaks from 6.8 ppm to 7.2 ppm) and a peak at 2.5 ppm appeared, which were attributed to the methyl groups in the durene skeleton. The integration of the NMR signals showed that the concentration of durene units relative to phenylene units was about 0.4% mol / mol, which was slightly lower than that in the initial reaction mixture. This may be related to the post-treatment procedures of the sample. Thermal properties of PPM-D (T g 65℃, starts to decompose at 410℃) is similar to PPM.

[0108] Comparison of 4-octoxy copolymer and tetramethylol copolymer

[0109] The comparison between coatings made of PPM copolymers containing 4-octoxy side chains and coatings of PPM copolymers containing BCMD was carried out according to ISO 17463:2014 rules (procedure reported below). However, the thickness of the two coatings tested was not equal, since the copolymers disclosed by D'Elia et al. can only be processed by hot pressing (which can only obtain thicker films). Thus, the thickness of the prior art coating was 30 μm, while the thickness of the novel coating obtained by spraying was only 20 μm. These tests revealed that during the preliminary EIS cycles, the coatings containing octoxy side chains had a |Z| 0.01Hz For 10 7 Ωcm 2 . In the following ACET cycle, it is observed that |Z| 0.01Hz and stabilized above 10 8 Ωcm 2 The value of Figure 7 ). Although the coating has good anticorrosion ability, after preliminary EIS |Z| 0.01Hz The increase in is attributed to the gradual saturation of the pores on the coating surface, reflecting the presence of inhomogeneities within the polymer film. This criticality of the coating becomes very important when the pre-damaged surface is exposed to the ACET test ( Figure 8 ). Despite the damage, the coating exhibited good corrosion protection (in the first two ACET cycles |Z| 0.01Hz The value is 10 7 Ωcm 2 to 10 8 Ωcm 2 ), but after the third cycle, the coating failed (|Z|0.01Hz About 10 4 Ωcm 2 ), with the subsequent generation of corrosion products. ACET tests performed on the surface of the coating made of PPM copolymer obtained using BCMD showed high corrosion protection (although 1 / 3 thinner than in previous tests) and high surface uniformity, which was well above 10 8 Ωcm 2 |Z| 0.01Hz reflect( Fig. 9 ).like Fig.10 ACET performed on pre-damaged surfaces showed that such coatings have a high protective capacity even after damage. This would be attributed to better self-healing.

[0110] Preparation of coating

[0111] Plates of high-strength aluminum alloy AA2024 (4.3% to 4.5% copper, 1.3% to 1.5% magnesium, 0.5% to 0.6% manganese and less than 0.5% other elements) with a length of 12 cm, a width of 3 cm and a thickness of 4 mm were provided by Aviometals.pa (Varese, Italy) and used as substrates. Samples with a length of 4 cm were cut and subsequently polished with 300 grit, 500 grit, 800 grit, 1200 grit and 4000 grit sandpaper. After polishing, the samples were immediately cleaned by immersion in ethanol in an ultrasonic bath (Banderlin, Berlin, Germany) for 5 minutes. The AA2024 sample was then removed from the ethanol bath and the residual alcohol on the surface was evaporated by nitrogen flushing.

[0112] A layer of benzyltriethoxysilane was coated on a freshly cleaned AA2024 sample by spin coating (3500 rpm, 30 s) and then heated to 100° C. for 1 min, whereupon the benzyltriethoxysilane condensed into the corresponding polysiloxane.

[0113] The copolymer coatings were made by pressing the polymer powder onto these silane pretreated AA2024 specimens, using a polyetheretherketone (PEEK) foil to separate the PPM-based polymer from the pressing apparatus. The octoxy copolymer (prior art) (13.4% mol / mol) was pressed at a temperature of 120°C for 30 seconds. The thickness was 30μm to 50μm. Although no rheological additives were added, the coating appeared very uniform and homogeneous. The BCMD copolymer coating (new) was obtained by dissolving the BCMD copolymer in chloroform to obtain a solution of 0.37g / mL. The solution was then prepared with p-xylene in a ratio of 3.9mL / mL (p-xylene / polymer solution). The preparation was applied to the unpretreated AA2024 surface at 120°C by spraying at a pressure of 0.5 bar.

[0114] Electrochemical characterization of coated AA2024

[0115] The anti-corrosion ability of the coating was studied by electrochemical technology, and AA2024 samples coated with two copolymers (octoxy (prior art) 13.4% mol / mol and BCMD (new) 0.4% mol / mol) were tested.

[0116] The electrochemical corrosion test was carried out in a naturally aerated near-neutral simulated marine environment by -1 Sodium chloride (≥99.0%, Sigma-Aldrich) was dissolved in prepared in water. By adding a few drops of 0.2 mol L -1 Sodium hydroxide solution, pH adjusted to 6.7 ± 0.1. Unless otherwise stated, all experiments were carried out at ambient temperature (24 ± 3 ° C, variation of less than 2 ° C per run). In all cases, the operating temperature was below the glass transition temperature of the copolymers according to the invention.

[0117] The device used for the measurement consisted of a glass cell with a hole (1 cm in diameter) in the middle of the flat bottom part, which ensured that the coated metal plate (working electrode, exposed area 0.78 cm 2 ) and the working solution (0.6 M NaCl). The seal was ensured by a double adhesive layer (a2 SoluzioniAdesive, Italy) pressed between the sample and the bottom of the cell. The electrochemical setup also included a platinum coil as counter electrode, a saturated calomel aqueous solution electrode as reference electrode (relative to SCE, E SCE = 0.242 V). The latter were inserted into a glass double bridge (filled with the same working solution) ending in a Luggin capillary intended to minimize the ohmic drop between working and reference electrodes. No instrumental compensation for the residual ohmic drop was performed.

[0118] Electrochemical characterization includes potentiodynamic and constant potential methods. The former includes anodic polarization scanning at 10 mV min -1 The potential was scanned from OCP to 2.5 V vs. SCE at a scan rate of 1.5 V (each time lasting about 5.5 h). 4 mA cm -2 The limiting current density is then independently terminated by reaching the final potential. The second characterization is to apply a constant potential to the metal sample and record the current between the working electrode and the counter electrode. In our experiments, an oxidation potential of 0 V relative to SCE was applied for 24 hours.

[0119] Potentiodynamic and potentiostatic curves were recorded after an initial delay time of 600 seconds to ensure the equilibrium of the system at OCP. Some potentiodynamic curves were also recorded at a fixed temperature of 35°C, just above the glass transition temperature of the copolymers according to the invention. For these experiments, a suitable cell surrounded by a jacket filled with water flow controlled by a thermostat (Haake CH Fisons coupled to Haake F3 Fision) was used.

[0120] For the accelerated scanning electrochemical technique (ACET), a preliminary controlled electrochemical impedance spectroscopy (EIS) was performed after conditioning at open circuit potential (OCP) for 10 min. The following polarization-relaxation-EIS sequence was repeated at least six times, one after another, according to the international standard ISO 17463:2014. The EIS analysis was performed in the frequency range from 100 kHz to 0.01 Hz, using a sinusoidal voltage of 10 mV as the amplitude of the open circuit potential (OCP). The following cathodic polarization step was performed at -2 V relative to SCE for 20 min; the relaxation process at OCP lasted for 3 h; and then a new EIS step was performed using the same mentioned parameters. The intrinsic self-healing and anti-corrosion properties of the PPM copolymer coatings were also studied by applying artificial circular scratches (hole diameter 0.52 mm, depth corresponding to the coating thickness) during the above conditioning time using the accelerated cyclic electrochemical technique. At the lowest frequency 0.01 Hz (|Z| 0.01Hz ) provides the impedance modulus of the coating. |Z| 0.01Hz (>10 7 Ωcm 2 ) reflects high anti-corrosion performance.

Claims

1. A copolymer comprising: The first monomer of formula (I) wherein Z1 is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3), and The second monomer of formula (II) in Z2 is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3), Y is selected from -CH2Z3, straight chain or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxy, -NHCOR5, -CONHR6, -OCOR7, -COOR8 and -OR9, wherein Z3 is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3); Wherein R5, R6, R7, R8 and R9 are selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 alkynyl; and R1, R2, R3 and R4 are independently selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxyl, oligo (C2 to C4 alkylene glycol), -NHCOR5, -CONHR6, -OCOR7, -COOR8 and -OR9, wherein R5, R6, R7, R8 and R9 are selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 Alkynyl.

2. The copolymer according to claim 1, wherein the second monomer has the general formula (IIa) in Z2 is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3), Z3 is selected from fluorine, chlorine, bromine, iodine, hydroxy, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3); and R1, R2, R3 and R4 are independently selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxyl, oligo (C2 to C4 alkylene glycol), -NHCOR5, -CONHR6, -OCOR7, -COOR8 and -OR9, wherein R5, R6, R7, R8 and R9 are selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 Alkynyl.

3. The copolymer according to claim 1 or 2, wherein Z2 and Z3 are the same.

4. A copolymer according to any one of the preceding claims, wherein Z1, Z2 and Z3 are identical, preferably chlorine.

5. A copolymer according to any one of the preceding claims, wherein R1, R2, R3 and R4 are the same, preferably methyl.

6. A copolymer according to any one of the preceding claims, wherein the copolymer comprises one or more additional monomers of formula (III) in Z2' is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3), Y' is selected from -CH2Z3', straight chain or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxyl, -NHCOR5', -CONHR6', -OCOR7', -COOR8' and -OR9', wherein Z3' is selected from fluorine, chlorine, bromine, iodine, hydroxyl, toluene-4-sulfonyloxy (-O-SO2-C6H4-CH3) and methylsulfonyloxy (-O-SO2-CH3); wherein R5', R6', R7', R8' and R9' are selected from a linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 alkynyl; and R1', R2', R3' and R4' are independently selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl, straight or branched C2-C 30 Alkynyl, sulfo (-SO3H), nitro, amino, hydroxyl, oligo(C2 to C4 alkylene glycol), -NHCOR5', -CONHR6', -OCOR7', -COOR8' and -OR9', wherein R5', R6', R7', R8' and R9' are selected from linear or branched C1-C 30 Alkyl, straight chain or branched C2-C 30 Alkenyl and straight or branched C2-C 30 Alkynyl, and in The monomer of the general formula (III) is different from the monomer of the general formula (II).

7. The copolymer according to any one of the preceding claims, wherein in the compounds of Formula II and Formula IIa, at least one of R1, R2, R3 and R4 is selected from a linear or branched C8-C 30 Alkyl, straight chain or branched C8-C 30 Alkenyl, straight or branched C8-C 30 Alkynyl and -OR9, wherein R9 is selected from a linear or branched C8-C 30 Alkyl, straight chain or branched C8-C 30 Alkenyl and straight or branched C8-C 30 Alkynyl.

8. The copolymer according to any one of the preceding claims, wherein the copolymer comprises 0.01% (mol / mol) to 5% (mol / mol), preferably 0.1% (mol / mol) to 1% (mol / mol), most preferably 0.5% (mol / mol) of the monomer of general formula (II).

9. A process for preparing a copolymer according to any one of the preceding claims, wherein the monomer of the general formula (I) and the monomer of the general formula (II) are copolymerized in the presence of a Lewis acid catalyst.

10. The method according to claim 9, wherein the catalyst is selected from bismuth (III) based catalysts, molybdenum based catalysts and tungsten based catalysts, preferably selected from WCl4(CNMe)2, WCl4(THF)2, WBr2(CO)3(dme) and MoI2(CO)3(MeCN)2.

11. The method according to any one of claims 9 and 10, wherein the polymerization of the monomer of general formula (I) The entire polymerization process is carried out in the presence of a catalyst, and The monomers of the general formula (II) are not added before at least 40% by weight of the monomers of the general formula (I) have reacted.

12. Use of the copolymer according to any one of claims 1 to 8 as a coating.

13. Use of the copolymer according to any one of claims 1 to 8 as a preservative.

14. A powder or paint comprising the copolymer according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Crosslinked polymers from alpha, alpha-dichloro-p-xylene and polysubstituted benzenes

    US3265640A